PI-like fuzzy based synchronous SEPIC converter control for PV-fed small scale irrigation DC pump. Issue 1 (1st January 2021) - Workineh, Tewodros Gera; Taye, Biniyam Zemene; Nebey, Abraham Hizikiel; Getie, Elias Mandefro
Abstract: For off-grid, standalone solar-fed water pumping has become a very viable option for small householder farmers. Appropriate configuration and control to suit this specific application are required. Buck, boost, and buck-boost converters are used to ensure impedance adaption between the solar PV generation and the load. However, these converters have switching harmonic problems. This problem is solved by the use of a single-ended primary inductor converter. Thus, a single-ended primary inductor converter is designed to overcome these drawbacks. Therefore, the objective of this paper is to design a single-ended primary inductive converter with a PI-like fuzzy controller. In this paper, synchronous SEPIC converter with PI-like fuzzy controller for PV-fed pumping system is modeled and designed. The system performance at different input conditions is evaluated. PI and PI-like fuzzy controllers have been compared using MATLAB/SIMULINK. PI-type fuzzy controller is less sensitive to input parameters variation than PI due to auto-tuning capability. Less than 2% output variation is recorded between 200 and 1000 W/m 2 irradiance. This show that output voltage is less sensitive to the input solar radiation with this SEPIC converter control. The steady-state result obtained in speed and flow rate were 141.4 rpm and 1.56 l/s, respectively, and the voltage error was 1.4 V. Thus, PI-like fuzzy controller was used to reduce the steady-state error. The results obtained with PI-like fuzzy controller in speed and flow rate were 143.6 rpm and 1.624 l/s at 6 m head, respectively. The voltage error is 0.2 V which is less than the PI converter error (1.4 V).